2018
DOI: 10.1007/s11356-018-2947-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tris(2,3-dibromopropyl) phosphate and other organophosphorous compounds in Arctic rivers

Abstract: The flame-retardant tris(2,3-dibromopropyl) phosphate (TDBrPP) was in the 1970s banned for uses in textiles that may be in contact with the skin, owing to strong suspicions that the substance was a human carcinogen. The substance is looked for but rarely detected in samples from the built and natural environments, but there are indications that TDBrPP is still in use. Here, we report the measurement of a polymer-water partition coefficient (K) for two types of silicone rubber (SR), allowing quantitative estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…39 TDBPP (∼48%) is the most abundant OPFR compound in the legacy site of Michigan Chemical, which produced this chemical 40 years ago. 40 It has also been widely detected at 100−200 pg/L in Arctic rivers, 41 indicating its LRAT potential.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…39 TDBPP (∼48%) is the most abundant OPFR compound in the legacy site of Michigan Chemical, which produced this chemical 40 years ago. 40 It has also been widely detected at 100−200 pg/L in Arctic rivers, 41 indicating its LRAT potential.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Similarly, Hu et al reported OPFRs in seawater of Yellow Sea and East China Sea, with the total concentrations ranging from 15.8 to 353.3 ng/L. Furthermore, surface water, including Arctic surface waters, was also reported among the reservoirs for OPFRs. , Meanwhile, Wang et al screened eight OPFRs in sediment samples from coastal Laizhou Bay of the Bohai Sea of China at a concentration ranging from 6.7 to 102 ng/g dry weight (dw). Due to the fact that the emissions into different environmental compartments are still increasing, the OPFRs can be considered as “emerging pollutants”. , Because of the increase in production and usage as well as their persistence and toxic nature, they have become a cause of concern and attracted attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surface water, including Arctic surface waters, was also reported among the reservoirs for OPFRs. 12,13 Meanwhile, Wang et al 14 screened eight OPFRs in sediment samples from coastal Laizhou Bay of the Bohai Sea of China at a concentration ranging from 6.7 to 102 ng/g dry weight (dw). Due to the fact that the emissions into different environmental compartments are still increasing, the OPFRs can be considered as "emerging pollutants".…”
Section: ■ Introductionmentioning
confidence: 99%
“…The general cleanup and GPC procedures have been described elsewhere 15,19 . Analysis for PRCs and OCs was performed on an Agilent 7890A gas chromatograph coupled to an Agilent 5975c inert XL EI/CI quadrupole mass spectrometer operated in single-ion monitoring mode (SIM) with electron impact ionisation (70 keV) 20,21 . Analyte separation was on a DB-5MS column (30 m, 0.25 mm inside diameter and 0.25 µm film thickness; Agilent JW Scientific) with a 1 µL pulsed split-less injection (pulse pressure 20 psi for 1.2 min and injector temperature of 300 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Quantification was performed using the relative response of surrogate internal standards and 7-point calibration curves. Deviation (< 20%) of the qualifier ion response relative to that of the quantifier ion was used for identification 21 For samplers analysed in the Czech Republic and in The Netherlands, we refer to previous work 16,22,23 .…”
Section: Methodsmentioning
confidence: 99%